Male hyraxes increase countersinging as strangers become 'nasty neighbours'. (December 2017) - Goll, Yael; Demartsev, Vlad; Koren, Lee; Geffen, Eli
Abstract : Many territorial animals interact less aggressively with neighbours than with strangers, a phenomenon known as the 'dear enemy' effect, although some species show the opposite behaviour. Rock hyraxes, Procavia capensis, are social mammals that communicate via a rich acoustic repertoire. Male hyraxes produce elaborate advertisement calls (i.e. songs) both spontaneously and in response to occasional attention-grabbing events (e.g. pup screams, agonistic interaction), as well as to conspecific male songs. When replying to conspecific songs, male hyraxes tend to respond more to familiar males than to strangers, reflecting the 'nasty neighbour' effect. Our study relates to the general question of why some species respond aggressively towards neighbours, while others are more aggressive towards strangers. We hypothesized that male hyraxes eventually familiarize themselves with a stranger, subsequently perceiving its intentions as highly threatening and deserving of a vocal response. To simulate the presence of a stranger in the area we exposed wild hyrax groups to playbacks of natural songs of unfamiliar hyraxes. Male rock hyraxes became more likely to reply to a stranger's song over time, but this was independent of the number of times they heard the song. This suggests that either (1) the threat presented by a stranger increases when it is no longer perceived as transient or (2) because listeners do not physically encounter the stranger, they perceive replying aggressively as a low-risk response. Our work implies that species may demonstrate a range of condition-dependent behaviours instead of a dichotomy between the 'nasty neighbour' and 'dear enemy' strategies. Highlights: Rock hyrax males increase their singing behaviour towards a stranger over time. We exposed wild hyraxes to sequential playbacks of unfamiliar hyraxes (strangers). Differing level of perceived threat may explain the change in response strategy. The dichotomy between species that respond to strangers/neighbours needs a review.